Electromyographic analysis of the rectus abdominis muscle in pelvic retroversion and the decrease of the lower limbs - de Cássia Pelizário Munhoz Martinelli, Rita; de Faria Negrão Filho, R. [UNESP]; Silva, A. C. (My University, 2008)
We often face Patients searching for rehabilitation for lower back disorders during the physiotherapeutic routine, and it is known that the abdominal muscle, specially the rectus abdominis muscle, aid the stabilization of the pelvis. Therefore, this paper analyzes the electrical activity of the rectus abdominis muscle in the pelvic retroversion in dorsal decubitus and in orthostatic position and in the lowering of the lower limbs. 30 healthy students, male and female, 17-40 yr, divided into two groups - Group 1: 15 volunteers (pelvic balance); Group 2 (pelvic unbalance) took part in this study. The electrical activity of the right and left supra-umbilical and infra-umbilical portions of the rectus abdominis muscle was detected. The mean RMS values from three attempts ftom the electromyographic traces were usedfor the analysis of the electrical activity. The RMS value was submitted to the normalization process. The data were submitted to statistic treatment by the Friedman test, and the analyses of the means and standard deviation towards a level of significance of 95%. The results demonstrated that the portions of the rectus abdominis muscle presented low electrical activity for the groups studiedfor pelvic retroversion either in dorsal decubitus or and orthostatic position. However, the decreasing movement of the lower limbs towards the portions of the rectus abdominis muscle presented more significant electrical activity whereas the lower portions presented higher activity than the higher ones for Group 2.
Keywords: Electromyography; Pelvic balance; Rectus abdominis muscle; adolescent; adult; biomechanics; body equilibrium; clinical article; controlled study; electromyography; female; Friedman test; head movement; human; leg movement; lordosis; male; muscle contraction; physiotherapy; rectus abdominis muscle; spine mobility; standing; supine position; task performance; Adolescent; Adult; Female; Humans; Leg; Male; Movement; Musculoskeletal Equilibrium; Pelvis; Posture; Rectus Abdominis